Efficacy and acceptability of noninvasive brain stimulation interventions for weight reduction in obesity: a pilot network meta-analysis - Zeng, Bing-Yan; Zeng, Bing-Syuan; Chen, Yen-Wen; Hung, Chao-Ming; Sun, Cheuk-Kwan; Cheng, Yu-Shian; Stubbs, Brendon; Carvalho, Andre F.; Brunoni, Andre R.; Su, Kuan-Pin; Tu, Yu-Kang; Wu, Yi-Cheng; et al. (International Journal of Obesity, 2021)
Background/Objectives: Obesity has recently been recognized as a neurocognitive disorder involving circuits associated with the reward system and the dorsolateral prefrontal cortex (DLPFC). Noninvasive brain stimulation (NIBS) has been proposed as a strategy for the management of obesity. However, the results have been inconclusive. The aim of the current network meta-analysis (NMA) was to evaluate the efficacy and acceptability of different NIBS modalities for weight reduction in participants with obesity. Methods: Randomized controlled trials (RCTs) examining NIBS interventions in patients with obesity were analyzed using the frequentist model of NMA. The coprimary outcome was change in body mass index (BMI) and acceptability, which was calculated using the dropout rate. Results: Overall, the current NMA, consisting of eight RCTs, revealed that the high-frequency repetitive transcranial magnetic stimulation (TMS) over the left DLPFC was ranked to be associated with the second-largest decrease in BMI and the largest decrease in total energy intake and craving severity, whereas the high-frequency deep TMS over bilateral DLPFC and the insula was ranked to be associated with the largest decrease in BMI. Conclusion: This pilot study provided a “signal” for the design of more methodologically robust and larger RCTs based on the findings of the potentially beneficial effect on weight reduction in participants with obesity by different NIBS interventions.